'Routledge (58) Argues …': A Quasi-Experimental Evaluation of Different Formats to Teach Students How to Reference. (May 2016) - Sarmiento-Mirwaldt, Katja
Referencing academic and other sources is a key study skill, but very little research has been dedicated to the effectiveness of different methods to teach students how to reference. This research seeks to determine which teaching methods are most effective in helping politics students to learn how to reference correctly. The research design is quasi-experimental: different students' ability to cite academic sources are mapped onto the same students' attendance at different learning activities dedicated to referencing. The analysis indicates that lecture-based and online methods, as well as group work in seminars, have no impact on students' ability to reference. While one has to bear in mind the limited internal validity of quasi-experiments, this research suggests that attending a one-to-one tutorial on referencing has a positive impact on students' ability to reference.